2017
DOI: 10.1093/scan/nsx080
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory control and impulsivity relate to resting frontal activity

Abstract: Gray’s Reinforcement Sensitivity Theory (RST) asserts three core personality systems: the behavioral approach system (BAS), the fight-flight-freeze system (FFFS) and the revised behavioral inhibition system (r-BIS). Past models of frontal activity link greater relative left frontal activity with Carver and White’s (1994) BAS scale and trait impulsivity and greater relative right frontal activity with Carver and White’s (1994) BIS scale. However, the original BIS scale assesses both FFFS and r-BIS. Past work li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 60 publications
5
52
3
Order By: Relevance
“…Another finding that replicated previous work was that individual differences in approach-motivated tendencies, measured by people's responses to the well-validated BIS/ BAS questionnaire, did not relate to individual differences in resting frontal asymmetry. This is consistent with some findings in the literature (Boksem et al, 2012;Neal & Gable, 2017;Wacker et al, 2010) that have also shown no relationship between BAS scores and frontal asymmetry, but is inconsistent with others (Coan & Allen, 2003;Harmon-Jones & Allen, 1997) that have shown associations between greater relative left frontal activation and higher BAS scores. However, frontal asymmetry did indeed show qualities of a stable individual difference measure here and has been shown in previous work to relate to approach motivation when there is a stronger emotional experience present (Wacker et al, 2010).…”
Section: The Role Of Frontal Asymmetrysupporting
confidence: 76%
See 1 more Smart Citation
“…Another finding that replicated previous work was that individual differences in approach-motivated tendencies, measured by people's responses to the well-validated BIS/ BAS questionnaire, did not relate to individual differences in resting frontal asymmetry. This is consistent with some findings in the literature (Boksem et al, 2012;Neal & Gable, 2017;Wacker et al, 2010) that have also shown no relationship between BAS scores and frontal asymmetry, but is inconsistent with others (Coan & Allen, 2003;Harmon-Jones & Allen, 1997) that have shown associations between greater relative left frontal activation and higher BAS scores. However, frontal asymmetry did indeed show qualities of a stable individual difference measure here and has been shown in previous work to relate to approach motivation when there is a stronger emotional experience present (Wacker et al, 2010).…”
Section: The Role Of Frontal Asymmetrysupporting
confidence: 76%
“…Price and Harmon-Jones (2010) also provided experimental evidence for the link between approach motivation and left hemisphere frontal activation by showing greater left versus right hemisphere frontal cortical activation when participants leaned forward with their arms extending forward (a high approach posture) compared with when they reclined backward (a low approach posture). Importantly, frontal asymmetry has also been related to individuals' BAS scores, as higher BAS scores have been associated with larger relative left resting frontal activity (Coan & Allen, 2003;Harmon-Jones & Allen, 1997), although this relationship has not always been found (Boksem, Kostermans, Tops, & De Cremer, 2012;Neal & Gable, 2017;Wacker, Chavanon, & Stemmler, 2010).…”
mentioning
confidence: 99%
“…A by now rather robust finding is the correlation of frontal asymmetry of the alpha band during rest with trait measures of inhibition, with reduced right frontal activity correlates with higher impulsivity (for a review see: Harmon-Jones, Gable, & Peterson, 2010; e.g., Neal & Gable, 2017). The correlation between self-reported impulsive aggression and frontal activity independent of frequencies has been not only been found in individuals with a criminal history, but also in undergraduate samples: students who self-reported impulsive aggressive behaviour showed a reduced right frontal alpha activity and relatedly an increased frontal asymmetry (Lake, Stanford, & Patton, 2014).…”
Section: Frequency Domain Based Eegmentioning
confidence: 99%
“…From a neuroanatomical perspective, impulse control is associated with prefrontal functioning. Several studies have shown that frontal dysfunction observed in the resting frontal cortical activity measured using quantitative electroencephalography (qEEG) was associated with increased impulsivity (9)(10)(11). Therefore, impulsive behavior, including NSSI, might be associated with frontal dysfunction.…”
Section: Introductionmentioning
confidence: 99%